Decomposition of carbon emission driving factors and judgment of peak status in countries along the Belt and Road - Li, Yuanmeng; Chou, Jieming; Zhao, Weixing; Xu, Yuan; Hao, Yidan; Jin, Haofeng (Frontiers in Environmental Science, 2023)
Most of the countries along the “Belt and Road” are still developing countries, and most of their carbon emissions have not yet reached their peak. However, there is currently a lack of comprehensive analysis and research to judge the current carbon peak state of the countries along the “Belt and Road” and quantify the contribution of key driving factors to the carbon emissions of the countries along the “Belt and Road”. This study fills this gap by developing a new method for judging the peak carbon status of a country based on the time series of carbon emissions. We divide the status of all countries along the Belt and Road into four categories: Has reached the peak, Peak plateau period1 (the downward trend is not significant), Peak plateau period2 (obvious recession), Not reached the peak. In addition, this study also uses the carbon emission database and socioeconomic database of countries along the Belt and Road from 2000 to 2019 to measure the driving factors of carbon emission changes in countries along the Belt and Road. To this end, based on the theory of Kaya's identity, we use LMDI factorization to decompose the change in carbon emissions of energy consumption into multiple factors: carbon intensity, energy intensity, economic output, and population size. The results show that the main positive driving factor of the three countries that have reached the peak is GDP PPP per population, while other driving factors make negative contributions to carbon emissions. However, in some years, these countries briefly experienced a negative contribution of GDP PPP per population to carbon emissions. The driving factors of the country's carbon emissions in the Peak plateau period play a role and are not stable. The contributions of GDP PPP per population, energy intensity and carbon intensity fluctuate periodically, sometimes positive and sometimes negative. In countries that have not reached the peak of carbon emissions, population growth and economic growth are very significant positive contributors to carbon emissions, and the effect of driving factors that negatively contribute to carbon emissions is not so obvious.